Give highly palatable and nutritious food.
Make sure the food smells right.
If you're feeding your dog kibble, add some warm water, bone broth, or wet food.
Offer home-cooked food.
Cut down on treats and avoid feeding off the table.
Praise the dog for eating the food.
Easy peasy pumpkineasy the answer issssssssssssssss 455555
Answer:
![\log_{10}(147) = 2.1673](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%202.1673)
Step-by-step explanation:
Given
![\log_{10} 3 = 0.4771](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%203%20%3D%200.4771)
![\log_{10} 5 = 0.6990](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%205%20%3D%200.6990)
![\log_{10} 7= 0.8451](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%207%3D%200.8451)
![\log_{10} 11 = 1.0414](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%2011%20%3D%201.0414)
Required
Evaluate ![\log_{10}(147)](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29)
Expand
![\log_{10}(147) = \log_{10}(49 * 3)](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%20%5Clog_%7B10%7D%2849%20%2A%203%29)
Further expand
![\log_{10}(147) = \log_{10}(7 * 7 * 3)](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%20%5Clog_%7B10%7D%287%20%2A%207%20%2A%203%29)
Apply product rule of logarithm
![\log_{10}(147) = \log_{10}(7) + \log_{10}(7) + \log_{10}(3)](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%20%5Clog_%7B10%7D%287%29%20%2B%20%5Clog_%7B10%7D%287%29%20%2B%20%5Clog_%7B10%7D%283%29)
Substitute values for log(7) and log(3)
![\log_{10}(147) = 0.8451 + 0.8451 + 0.4771](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%200.8451%20%2B%200.8451%20%2B%200.4771)
![\log_{10}(147) = 2.1673](https://tex.z-dn.net/?f=%5Clog_%7B10%7D%28147%29%20%3D%202.1673)
Answer:
a vertical shift of 6 units up
Step-by-step explanation:
We have the transformation:
g(x) = f(x) + k
This is what we call a vertical shift, this transformation moves the graph of f(x) k units, and the motion is upwards if k is positive, and downwards if k is negative.
Here we can see that the graph of f(x) intersects the y-axis at y = -2
While the graph of g(x) intersects the y-axis at y = 4.
Then the distance between these two points is:
4 - (-2) = 6
This means that the graph of g(x) is 6 units above the graph of f(x)
Then we have that k must be equal to 6, then the transformation is:
g(x) = f(x) + 6
This is a vertical shift of 6 units up.
Cody: 2x
Evan: x
x-7 (Evan’s age 7 years ago (-7))
2x-7( Cody’s age 7 years ago (-7))
So you add both
x-7+2x-7
And that should equal 7 (seven years ago the sum of their age was 7)
x-7+2x-7=7
3x-14=7
3x=21
x=7
Evan (x)= 7
Cody (2x)= 7 times 2
Cody= 14